The Notion of Soul according to Edith Stein in “The Structure of the Human Person”. Continuity and Novelty (Teología, 2018)
Some chapters of the last course in anthropology delivered by philosopher Edith Stein, before she embraced contemplative life in the Carmel, allow the revelation of continuities and novelties regarding Aristotle and Saint Thomas of Aquinas in relation with the notion of soul and its integrating function. Some coincidences among the three philosophers are enumerated in the first place, in order to show later the particular approach of each of them, highlighting the independence of criterion and the originality of Saint Thomas over Aristotle and of Edith Stein over both. The different manners of understanding the soul as act and as form and its link with the body are reviewed, showing that the heritage of vocabulary that may aim at dualism does not invalidate the thesis of the substantial unity of the living being.
Keywords: Aristotle; Saint Thomas of Aquinas; Edith Stein; Saint Teresa Benedict of the Cross; Soul; Body; Human person; Anthropology; Metaphysics